A comparative study of common carp (Cyprinus carpio L.) and calbasu (Labeo calbasu Hamilton) on bottom soil resuspension, water quality, nutrient accumulations, food intake and growth of fish in simulated rohu (Labeo rohita Hamilton) ponds - Rahman, Mohammad Mustafizur; Jo, Qtae; Gong, Yeong; Miller, Stephanie A.; Hossain, Md. Yeamin (Wiley-Blackwell, 2008)
The effects of two benthivorous fishes, common carp (Cyprinus carpio) and calbasu (Labeo calbasu), on bottom soil resuspension, water quality, nutrient accumulations, fish diet and growth of rohu (Labeo rohita) were compared. In this study, individual tanks receiving bottom soil and water from a central pond were used to more naturally simulate rohu polyculture pond conditions. Two treatment combinations were performed in triplicate for 4 weeks: 6 rohu plus 3 common carp per tank and 6 rohu plus 3 calbasu per tank. Resuspension of bottom soil, free CO2, and nitrogen and phosphorous concentrations in the water column were greater in the tanks with common carp while dissolved oxygen, pH, and total alkalinity were lower. Common carp increased the % nitrogen and % phosphorous accumulation in plankton and fish, while these nutrients were reduced in benthic macroinvertebrates and bottom soil. Gut contents of harvested calbasu contained a combination of benthic macroinvertebrates and zooplankton, rohu contained phytoplankton and zooplankton, and common carp contained almost entirely (82%) macroinvertebrates. Rohu shifted from zooplankton to phytoplankton when competition for zooplankton was higher in calbasu tanks. Since common carp preferred benthic macroinvertebrates they overlapped little with rohu for food. Common carp increased the harvesting weight and growth rate of rohu and thus had greater potential than calbasu to increase yields for rohu polyculture farmers.